2016
DOI: 10.18632/oncotarget.8979
|View full text |Cite
|
Sign up to set email alerts
|

TAZ and YAP are frequently activated oncoproteins in sarcomas

Abstract: TAZ (WWTR1) and YAP are transcriptional coactivators and oncoproteins inhibited by the Hippo pathway. Herein we evaluate 159 sarcomas representing the most prevalent sarcoma types by immunohistochemistry for expression and activation (nuclear localization) of TAZ and YAP. We show that 50% of sarcomas demonstrate activation of YAP while 66% of sarcomas demonstrate activated TAZ. Differential activation of TAZ and YAP are identified in various sarcoma types. At an RNA level, expression of WWTR1 or YAP1 predicts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 42 publications
6
105
0
Order By: Relevance
“…A recent study had unraveled that overexpression of PRMT1 downregulates the phosphorylation of LATS1 and YAP, indicating that PRMT1 inhibits EMT probably via Hippo signaling . Moreover, expression profiles of the core Hippo signaling components in sarcomas were also reported . But the mechanism by which the Hippo pathway was regulated was largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study had unraveled that overexpression of PRMT1 downregulates the phosphorylation of LATS1 and YAP, indicating that PRMT1 inhibits EMT probably via Hippo signaling . Moreover, expression profiles of the core Hippo signaling components in sarcomas were also reported . But the mechanism by which the Hippo pathway was regulated was largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, YAP is considered as a prognostic factor for overall survival in patients with colorectal and hepatocellular carcinoma . Recently, loss of expression of the Hippo kinases is frequent while YAP/TAZ are frequently activated oncoproteins in sarcomas . These reports have implied that deregulation of the Hippo signaling or activation of YAP/TAZ is a frequent event in tumor biology and may be implicated in the pathogenesis of chondrosarcoma, and certainly merits further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments showed that verteporfin suppressed the viability and proliferation of all three MLS cell lines analyzed in a dose-dependent manner ( Fig 5A, Table 1). The growth-inhibitory effects of verteporfin could be attributed to increased apoptosis and a significant reduction in mitotic activity, as assessed by flow cytometric quantification of cleaved PARP and phosphorylated histone H3 S10 , respectively ( Fig 5B, Table 2), and were accompanied by reciprocal dose-dependent changes in the expression of the YAP1 downstream effectors FOXM1 and PLK1 ( Fig 5C) (Eisinger-Mathason et al, 2015;Fullenkamp et al, 2016). Finally, TEAD reporter assays demonstrated that verteporfin significantly decreased luciferase activity in MLS cell lines co-transfected with a constitutively active YAP1 S127A mutant ( Fig 5D).…”
Section: Sensitivity Of Mls Cells To Pharmacologic Inhibition Of Yap1mentioning
confidence: 99%
“…30 Thus, it is understandable that dysregulations of the Hippo pathway occur in many bone and soft tissue sarcomas. 31,32 However, only a few oncogenic mutations are found in the Hippo pathway that result in its dysregulation. Instead, the most likely cause of perturbed Hippo signaling in sarcoma is the cross-talk with commonly mutated cancer genes such as KRAS, PIK3CA, CTNNB1, or FBXW7.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
“…33 In tissue microarray samples of human sarcomas, both YAP and TAZ are expressed in variety of tumors, including Ewing's sarcoma. 31 YAP expression in Ewing's sarcoma is positively correlated with the expression of polycomb protein (BMI-1), which promotes the tumorigenicity of Ewing's sarcoma. YAP expressions levels are maintained and do not diminish in confluent Ewing's sarcoma tumor cells that express high levels of BMI-1.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%